The role of meat in the European diet: current state of knowledge on dietary recommendations, intakes and contribution to energy and nutrient intakes and status. Issue 2 (10th December 2020) - Cocking, Chris; Walton, Janette; Kehoe, Laura; Cashman, Kevin D.; Flynn, Albert
Abstract: The role of meat in the diet has come under scrutiny recently due to an increased public emphasis on providing healthy diets from sustainable food systems and due to health concerns relating to the consumption of red and processed meat. The present review aimed to summarise dietary guidelines relating to meat, actual meat intakes and the contribution of meat to energy and nutrient intakes of children, teenagers and adults in Europe. The available literature has shown that food-based dietary guidelines for most countries recommend consuming lean meat in moderation and many recommend limiting red and processed meat consumption. Mean intakes of total meat in Europe range from 40 to 160 g/d in children and teenagers and from 75 to 233 g/d in adults. Meat contributes to important nutrients such as protein, PUFA, B vitamins, vitamin D and essential minerals such as Fe and Zn; however, processed meat contributes to significant proportions of saturated fat and Na across population groups. While few data are available on diaggregated intakes of red and processed meat, where data are available, mean intakes in adults are higher than the upper limits recommended by the UK Scientific Advisory Committee on Nutrition (70 g/d) and the World Cancer Research Fund (500 g/week). While there are no recommendations for red and processed meat consumption in children and teenagers, intakes currently range from 30 to 76 g/d. The present review provides a comprehensive overview of the role of meat in the European diet which may be of use to stakeholders including researchers, policy makers and the agri-food sector.